Use of Some Basic Dyes in the Extractive Spectrophotometric Determination of Tranexamic Acid - Baby Sudha Lakshmi, P.; Vardhan, S.V.M.; Ramachandran, D.; Rambabu, C. (Asian Journal of Chemistry, 2010)
A simple and sensitive spectrophotometric method is developed for the determination of tranexamic acid. It is based on the formation of coloured ion-pair complex between the tranexamic acid and basic dyes (methylene blue, methylene violet and saframin-O) in the aqueous phase at suitable pH extractable into chloroform showing the characteristic absorption maximum at 650, 550 and 520 nm, respectively. The method has been applied to pharmaceutical formulations. The method has been statistically validated and is found to be precise and accurate.